A mink (Neovison vison) model of self-injury: Effects of CBP-CREB axis on neuronal damage and behavior - Liu, Chunxiao; Guo, Xiaolan; Si, Huazhe; Li, Guangyu (Frontiers in Veterinary Science, 2022)
Objective Self-injurious behavior (SIB) is a clinically challenging problem in the general population and several clinical disorders. However, the precise molecular mechanism of SIB is still not clear. In this paper, the systematic investigation of the genesis and development of SIB is conducted based on behavioral and pathophysiology studies in mink (Neovison vison) models. Method The night-vision video was used to observe the mink behavior, and the duration was a month. HE stain was performed to characterize the pathology change in the brain of a mink. IHC assay was performed to conduct the protein level detection of Iba-1, p-CREB, CBP, and p300 in the brain tissues. Elisa assay was used to examine the levels of NfL and NfH in serum and CSF of mink. The qRT-PCR assay was used to detect the expression of Bcl-2, NOR1, FoxO4, c-FOS, CBP, and p300 in brain tissues. Western blot was used to detect the protein levels of p-CREB, CBP, and p300 in brain tissues. We also used Evans Blue as a tracer to detect whether the blood-brain barrier was impaired in the brain of mink. Result The behavioral test, histopathological and molecular biology experiments were combined in this paper, and the results showed that CBP was related to SIB. Mechanism analysis showed that the dysregulation of CBP in brain-activated CREB signaling will result in nerve damage of the brain and SIB symptoms in minks. More importantly, the CBP-CREB interaction inhibitor might help relieve SIB and nerve damage in brain tissues. Conclusion Our results illustrate that the induction of CBP and the activation of CREB are novel mechanisms in the genesis of SIB. This finding indicates that the CBP-CREB axis is critical for SIB and demonstrates the efficacy of the CBP-CREB interaction inhibitor in treating these behaviors.